WordPress : the missing manual - MacDonald, Matthew (Missing manual., 2023)
Whether you're a budding blogger or seasoned web designer, WordPress is a brilliant tool for creating websites-once you know how to tap into its impressive features. The latest edition of this jargon-free Missing Manual shows you how to use WordPress's themes, widgets, and plug-ins to build just about any kind of site. The important stuff you need to know: Set up WordPress: Configure WordPress on your web host or get it running on your home computer. Create your site: Get hands-on instructions for building all types of websites, from blogs to business sites with ecommerce features. Jazz it up: Add picture galleries, slideshows, video clips, music players, and podcasts. Add features: Select from thousands of plug-ins to enhance your site's capabilities, from contact forms to a basic shopping cart. Build a truly unique site: Customize a WordPress theme to create a site that looks exactly the way you want. Attract an audience: Use SEO, site statistics, and social sharing to reach more people. Stay safe: Use backup and staging tools to protect your content and avoid catastrophe.